PERENCANAAN PENINGKATAN KUALITAS PERMUKIMAN DI KECAMATAN ILIR BARAT DUA KOTA PALEMBANG - Deven Hanyaken; Abdullah Qiqi Asmara; Rosidawani Rosidawani; Elias Pikal; Fajar Sadik Islami (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Tridinanti, 2025)
Better basic public service infrastructure is needed for the growth of the housing and settlement sector. Housing infrastructure is needed along with the growth of an area. Infrastructure that functions as a center of citizen activity plays an important role in improving the urban environment. Palembang City is one of the metropolitan cities that also has problems with the quality of settlements, namely slum areas. In this study, a study was conducted on improving the quality of settlements in slum areas in Ilir Barat Dua District which focused on the areas of Tiga-puluh Ilir Village and Tiga-puluh-dua Ilir Village. The research method used was literature study, field study conducting data inventory with direct observation and stages of preparing a settlement quality improvement plan in accordance with regional spatial planning. The results of the slum indicators obtained that the waste management system, drainage system and environmental roads were the highest factors with values of 86%, 66% and 30% for Tiga-puluh Ilir Village, respectively. Meanwhile, for Kelurahan Tiga-puluh-dua Ilir also obtained the largest slum indicators, namely the waste management system of 81%, the quality of the environmental road surface of 70% and the availability of drainage of 51%. Seeing these results, the main focus of planning to improve the quality of settlements is on drainage channels and road access.